Audit firm attributes and income smoothing: the moderating influence of audit committee accounting expertise - Hussaini Bala; Waqar Ahmad; Ghousia Khatoon; Abubakar Balarabe Karaye (Cogent Business & Management, 2022)
This study investigates how audit committee accounting expertise (ACAE) influences the relationship between audit firm attributes (AUFA) and income smoothing (IS). The study employed 616 firm-year observations from 2013 to 2019 and robust logistic regression as a data analysis technique. The results showed that audit fees (AUF) are likely to decrease IS. The study also found that Big 4 auditors and audit tenure (AUT) might not reduce the likelihood of IS. Interestingly, Big 4 auditors and AUT had a negative and significant relation with IS in firms with a higher proportion of ACAE. The study revealed that a higher proportion of ACAE overturned the positive effect of Big 4 auditors and AUT on IS. The study provides a unique understanding of the moderating effect of ACAE on the link between AUFA and IS. The study makes distinctive contributions by exploring the moderating effect of ACAE on the link between AUFA and IS practices in Nigeria. Previous studies on income manipulation generally focus on accrual earnings; this study provides an insight into earnings manipulation through artificial smoothing indices. Policymakers and investors can benefit from the study's findings in formulating policies or decisions about corporate financial reporting issues. The study is limited to nonfinancial firms; therefore, the study's findings may not apply to financial firms.
Keywords: 650; audit committee accounting expertise; Audit firm attributes income smoothing